Comprehensive Study of Shape of Channels Filled with Porous Materials in Streaming Potential Cells - Ryota KIRINO; Suguru IWAI; Kosuke SATO; Elena VILLANI; George HASEGAWA; Shinsuke INAGI (Electrochemistry, 2025)
Streaming potential is the potential difference established between the inlet and outlet of a narrow channel while pumping a low-concentration electrolyte and is used in various applications, such as power generation devices, zeta potential analyzers, and electrochemical reactions. However, the effects of cell parameters, such as the geometry and resistance of channels with porous fillers, on streaming potential generation have not been clarified. Herein, the effects of the shape of a channel filled with a porous phenolic resin monolith material on streaming potential and current generation behavior were comprehensively investigated. Additionally, the energy conversion efficiency of streaming potential generation using a cell based on this channel was elucidated.